Synthesis, structural elucidation, fire retardancy and mechanical properties of cyclotriphosphazene derivatives blended with polyurethane lacquer as wood coatings - Nurul Atiqah Mohd Taip; Zuhair Jamain; Ismawati Palle (Malaysian Journal of Chemistry, 2025)
This study synthesized cyclotriphosphazene derivatives and evaluated their fire retardancy and mechanical properties for use in wood coatings. Two hexasubstituted cyclotriphosphazene derivatives with dodecyl and hydroxy groups were successfully synthesized. These compounds were subsequently characterized by FTIR and NMR spectroscopy and CHN elemental analysis. The thermal stability of the cyclotriphosphazene compounds was assessed using TGA, while the fire-retardant properties of each coating were evaluated through LOI. Both compounds exhibited good fire retardancy compared to pure epoxy resin, with LOI values of 24.71 (dodecyl) and 25.80 (hydroxy) wt.%, respectively. The LOI results show that coatings made with these nitrogen- and phosphorus-containing compounds demonstrated a significantly improved retardant effect when combined with polyurethane lacquer, compared to polyurethane alone. In addition, the physical and mechanical properties of these derivatives were analysed to assess potential drawbacks of the additives. The essential indicators of the quality of the lacquered wood panel surfaces were: the determination of resistance to household chemicals (ASTM D 1308-2), determination of temperature change resistance (ASTM D1211-97 (2001)), determination of adhesion: cross-cut test (ISO 2409-2007(E)), determination of impact (BS 3962 Part 6:1980) and determination of abrasion (ASTM 4060-10). These tests revealed that the performance of the surface coating systems was significantly influenced by the coating formulation.